Studi Pembuatan Chocolate Lava Cake Berbahan Dasar Tepung Sorgum dan Tepung Singkong - Esteria Priyanti; Puji Rahayu (Garina, 2021)
The aims of this study were 1) to determine the level of preference for the taste, aroma, texture and color of chocolate lava cake made from sorghum flour and cassava flour; and 2) knowing the composition of the chocolate lava cake ingredients based on sorghum flour and cassava flour which is the most preferred by the panelists. The methods used consist of library methods, experiments and hedonic tests. Result of the research to be explained descriptively. The results showed that the most preferred product by the panelists was 50% sorghum flour and 50% cassava flour. The average value of the product preference level is 4.73±0.81 (very like) for taste, 4.20±0.66 (very like) for aroma, 4.47±0.63 (very like) for texture and 4.73±0.58 (very much like) for color. The composition of chocolate lava cake is classified into the composition of the ingredients for the cake and the cake filling. The composition of the cake ingredients consists of 450 g dark cooking chocolate, 200 g brown sugar, 170 g olive oil, 50 g cocoa powder, 30 g sorghum flour, 30 g cassava flour, 20 g milk powder, 4 eggs, and ½ tsp baking powder. The composition of the cake filling ingredients consists of 200 g dark cooking chocolate and 15 g olive oil. It can be concluded, the selected product can be an alternative to healthy food products.